Impact of Typhoon Talim on surface sediment records on the East China Sea continental shelf. (30th September 2021) - Lu, Jian; Li, Anchun; Dong, Jiang; Feng, Xuguang; Pei, Wenqiang
Abstract: The East China Sea (ECS) is susceptible to summer typhoons, which play an important role in sediment transport and reworking on the continental shelf. However, because observations during typhoon passage are difficult to carry out even at present, the influence of typhoons on sedimentary records in the ECS is not fully understood. In this study, we compared the elemental compositions and grain-size distributions of surface sediments collected before and after the passage of Typhoon Talim. Through end-member modeling algorithm (EMMA) analysis, the variations in sediment composition due to the typhoon passage were characterized, and the impacts of typhoons on sediment migration, redistribution and sedimentary records on the ECS continental shelf were elucidated. Comparison of the results revealed that after the passage of Typhoon Talim, the clay distributions were generally parallel to the coastline, the sand contents in the northeast and southeast of the study area decreased, and the sorting coefficient decreased in the inner shelf mud area and increased in the relict sand area. The three-end-member model was capable of adequately reproducing all variables, and the three end members were interpreted to be the fine-grained components of river terrigenous sediments (EM1), mixed sediments (EM2), and relict sands (EM3) according to the grain-size and chemical element composition characteristics of surface sediments. Summer typhoons can interrupt the cross-shelf transport of fine-grained sediments caused by cross-shelf penetrating fronts (CPFs) and can promote exchange between fine-grained sediments and relict sands on the ECS continental shelf. Thus, summer typhoons play a vital role in retaining the mud on the ECS inner shelf and redistributing the sediments on the ECS continental shelf. Highlights: Grain sizes of surface sediments were analyzed before and after Typhoon Talim. Three grain-size end members were discerned by EMMA analysis. The cross-shelf transport of sediments could be interrupted by summer typhoons. Summer typhoons promoted the exchange of sediments on the ECS shelf.